Efektivitas Intervensi Reward dan Punishment Behavioristik dalam Pembentukan Karakter Tanggung Jawab pada Anak Sekolah Dasar - Musdalifah Musdalifah; Ulfiani Rahman (CV. Rayyan Dwi Bharata, 2025)
This study analyzes the effectiveness of behavioristic reward and punishment interventions in developing responsibility character among elementary school children in Indonesia. The research objectives are to identify the most optimal types of rewards and punishments and factors moderating their effectiveness. The study was conducted through systematic literature review of scientific journals from 2020-2024 using Google Scholar, JSTOR, ScienceDirect, Garuda Portal, and SINTA databases. Results indicate that verbal and non-verbal rewards effectively enhance student motivation and responsibility, while educational punishment provides positive impacts without damaging self-esteem. A balanced combination of reward and punishment yields optimal results with 61.4% contribution to character development. The study concludes that consistent implementation, adjusted to children's developmental stages, and involving teacher-parent collaboration are key success factors in developing responsibility character in elementary schools.